Analysis of student learning difficulties of first high school series from a state school (Research, Society and Development, 2020)
This paper aims to analyze the learning difficulties of the students of the 1st grade of a high school of a state school in the city of Maranguape, Ceará State, Brazil. It addresses the pedagogical procedures of this school, which currently aim to overcome or at least minimize learning difficulties, especially in the subjects of Mathematics and Portuguese Language. A field research was used for the analysis of this problem, taking as reference the qualitative research, using the questionnaire technique conducted with 04 (four) students target audience of the analyzed series, and interview with 04 (four) teachers in the school year. of 2019 and a bibliographical investigation, with support in Piaget (1985), Vygotsky (1991), Wallon (1975), Goméz & Terán (2009), among others, in institutional documents. The results indicate that the learning difficulties observed are reflective of attention deficit, hyperactivity, lack of stimulation of the school environment and also low academic performance of students in previous grades of elementary school, causing failure in high school. Unanimously, the teachers interviewed consider the lack of continuing education as an obstacle to the improvement of their practices that need to be updated and reformulated so that they can conduct their work more specifically, considering the peculiarities of each student's development, in order to rescue interest, willingness and motivation in their school activities. We conclude that it is evident the learning difficulties in the first grade of high school and that strategies and pedagogical interventions are necessary to minimize this problem in the researched environment.